Sefâkusî'nin Fâtiha Sûresindeki Kur'ân kıraatlerine morfolojik direktifleri - Alnaka, Abdulrahman (Yakup YILMAZ, 2022)
Linguists was highly interested in the topic of morphological orientation to the Quranic readings throughout generations. They also had specialized many books which delt with the orientation of Mutawatar readings and Shaz readings. One of those scholars was a widely known great linguist by the name of Ibrahim al-Safaqisi who had written in both topics, namely, the mutawatar and the Shaz readings of the Quran.In this thesis we focused on his morphological orientations which we derived from his “al-Mujeed fi I’rab al-Quran al-majeed” namely book and especially in surat Al-Fatiha; we studied and analyzed his morphological thoughts due to its importance. We found that he had mentioned four types of morphological examples: the lightening of the (ya) character in the word (Iyyaka) to run from the multiplication of the letter he also changed the hamza character into a ha, as well, he changed the sin letter in the word (sirata) into sad or zay. Additionally, he changed the alef letter in the word (daleen) into a hamza character and the Mudara’a letter in the words (na’budwanasta’in) into a kasra mark. The importance of the topic lies in showing how far the quranic readings harmonizes with the Arabic language’s rules the thing which helps in straightening out the readings.

Dilbilimciler, Kur'ân kıraatlerinin morfolojik tevcîhâtına geniş ilgi göstermişlerdir. Eserlerinde farklı kıraatleri el almışlar, eleştirmişler veya delil olarak kullanmışlardır. Ayrıca mütevâtir ve şaz kıraatlerin tevcîhâtıyla ilgiliçok sayıda müstakil kitap yazmışlardır.Bu seçkin âlimlerin arasında büyük dilbilimci İbrahim Sefâkusî de vardır. O, hem mütevâtir hem de şaz kıraatlerin tevcîhâtı ile ilgili eser telif etmiş ve bu alanda söz sahibi bir âlim olarak ön plana çıkmıştır. Bu çalışmada onun El-Mecid fi İrabi'l Kur'an'il Mecid adlı kitabındaki Kur'ân kıraatleri ile ilgili morfolojik tevcîhâtı Fâtiha suresi özelinde incelenecektir. Fâtiha suresindeSefâkusî dört morfolojik örnek üzerinde durmuştur. Bunları şu şekilde özetleyebiliriz: (İyyeke) إياك kelimesinde şeddeden kurtulmak için ye harfini tek harekeli yapmak ve hemzeyi he harfine çevirmek; (Sırat) الصراط kelimesinde sin harfini sad harfine veye zey harfine çevirmek; (El Dalliin)الضالين kelimesindeki elif harfini hemzeye çevirmek; (Na'bud ve Nesta'in) نعبد ونستعين kelimelerinde muzari harflerine kesre getirmek. Çalışma, kıraatlerin zaptına yardımcı olan Arap dilinin kıraatlerle ne ölçüde uyumlu olduğunu göstermesi açısından önemlidir.

عُني علماء اللّغة بالتوجهات الصرفيّة للقراءات القرآنيّة عناية واسعة، وعُنوا بنقلها وتوجيهها والاحتجاج بها أو لها، وقد أفردوا فيها كتباً كثيرةً فيما يتعلق بتوجيه القراءات المتواترة كما صنّفوا في توجيه القراءات الشاذة أيضاً، ومن هؤلاء العلماء الأجلاء إبراهيم الصفاقسي، العالم اللغوي الكبير، فقد صنّف في كليهما، أعني: توجيه القراءة المتواترة والشاذة معاً، حتى ذاع صيته في هذا المجال وعلتْ منزلتُه، وإنّي وجهتُ اهتمامي إليه، أستقي من كتابه المجيد في إعراب القرآن المجيد توجيهاته الصرفيّة للقراءات القرآنيّة في سورة الفاتحة ودراستها وتحليلها نظراً لأهمّيتها وما تضمّنته من مسائل صرفية مُهمة وتعدد أوجه القراءات فيها، وأصل هذا البحث جزء من أطروحتي في الدكتوراه، فقد ذكرتُ فيه النماذج الصرفية التي وقف عندها الصفاقسي في هذه السورة، حيث كانت تشتمل على نماذج أربعة، وهي: تخفيف الياء فراراً من التضعيف في كلمة (إياك) وأيضاً إبدال الهمزة فيها هاء، وإبدال السين صاداً أو زاياً في كلمة (الصراط)، وقلب الألف همزة في كلمة (الضالين) وكذلك الحديث عن كسر أحرف المضارعة في كلمتي (نعبد ونستعين). وتكمن أهميّة الموضوع في بيان مدى موافقة القراءات لأوجه اللغة العربية وهو ما يساهم في ضبط القراءات.
Keywords: Quranic Readings; morphological orientation; Arabic language; al-fatiha; al-Safaqisi; Arap Dili; Sefâkusî; Kur; Morfolojik Tevcîhât; Fatiha; اللغة العربية; الصفاقسي; القراءات القرآنية; التوجيه الصرفي; الفاتحة; Linguistics; Dilbilim